2022
DOI: 10.1097/prs.0000000000009723
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Breast Sensation between Alloplastic and Autologous Breast Reconstruction Patients using the BREAST-Q Sensation Module

Abstract: Background: Sensory recovery of the breast is a compelling frontier in comprehensive postmastectomy breast reconstruction. This study uses the BREAST-Q Sensation Module to evaluate the differences in women who underwent an alloplastic versus autologous breast reconstruction. Methods: Women with a history of breast cancer and postmastectomy breast reconstruction were recruited through the Love Research Army, United States. Participants completed the BREAST-Q Sensation Module, which consists of three scales: B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…These results validate former studies comparing postmastectomy sensation between autologous and alloplastic cohorts. 7,9,20 A likely component of the improved sensation in the autologous cohort was the neurotization of the abdominal flap to the third intercostal nerve using a nerve allograft. Djohan et al 22 demonstrated that breasts reconstructed with abdominal flaps which have been neurotized in a similar fashion develop increased sensation compared with nonneurotized controls.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These results validate former studies comparing postmastectomy sensation between autologous and alloplastic cohorts. 7,9,20 A likely component of the improved sensation in the autologous cohort was the neurotization of the abdominal flap to the third intercostal nerve using a nerve allograft. Djohan et al 22 demonstrated that breasts reconstructed with abdominal flaps which have been neurotized in a similar fashion develop increased sensation compared with nonneurotized controls.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] The breasts play a critical role in a woman's sexual health and self-image; previous studies on patient-reported outcomes using the BREAST-Q survey have found that restoring breast sensation can significantly improve quality of life. 9,10 Furthermore, the lack of protective sensation can predispose patients to injury; for example, thermal burns from common household items due to breast numbness have been reported in the literature. 11,12 Previous studies on breast sensation have elucidated the effects of mastectomy and reconstructive techniques on sensation, as well as the impact of neurotization techniques in both autologous and alloplastic reconstruction.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…9 As shown in previous studies using the BREAST-Q sensation module, restoring breast sensation can significantly impact quality of life. 10 Furthermore, breast anesthesia can also lead to incidental injuries, such as trauma and burns, because of the lack of sensory feedback and disrupted regulation of blood flow's thermal dynamics in anesthetized skin. 11,12 In our previous study, we explored differences in sensory recovery between neurotized deep inferior epigastric perforator (DIEP) flap reconstruction and implant-based reconstruction.…”
mentioning
confidence: 99%